IMPLEMENTASI KEBIJAKAN PERDA NOMOR 13 TAHUN 2019 TENTANG PENGELOLAAN SAMPAH DI KECAMATAN CIPUTAT KOTA TANGERANG SELATAN - Dwi Juliani, Astika; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
The waste problem is one of the things that cannot be avoided in the lives of the people of South Tangerang City. The geographical area that borders the DKI Jakarta Province and low public awareness means that the number of waste problems in South Tangerang City is still low. South Tangerang City Government continues to make efforts to reduce waste problems through Regional Regulation Number 13 of 2019 concerning Waste Management. It is hoped that the formation of this regulation will be able to increase the city's resilience in maintaining public health and turning waste into a resource as well as significantly reducing the volume of waste in South Tangerang City. This research aims to analyze the implementation of Regional Regulation Number 13 of 2019 concerning Waste Management and analyze the driving and inhibiting factors in its implementation in Ciputat District, South Tangerang City. The research method used in this research is descriptive qualitative using primary data sources obtained through in-depth interviews and field observations as well as secondary data. In this study, researchers analyzed the implementation of Regional Regulation Number 13 of 2019 concerning waste management through the phenomenon of policy content and policy environment. In this research, it was found that the process of implementing Regional Regulation Number 13 of 2019 concerning waste management had been carried out with the problems faced by the South Tangerang City Government. The implementation of Regional Regulation Number 13 of 2019 concerning waste management has also gone well although there are still obstacles regarding the implementation system. In implementing this program there are also driving factors, namely resources and bureaucratic structure, as well as inhibiting factors, namely communication and disposition.